Centralising the Marginalised through Magical Realism in Moustache by S. Hareesh - Khoche, Pranav (Integrated Journal for Research in Arts and Humanities, 2024)
The present paper attempts to present how Vavachan, a youth belonging to Pulayan community, considered a lower caste in Kerala, becomes a legendary character Moustache and gets centralized in the narrative through the use of magical realism in the novel Moustache (2020) by S. Hareesh. The paper also tries to show how folklore, myths and songs created about him in the novel present him as a man with supernatural powers rather than a common vagabond. The paper in a way tries to elucidate how the status of the marginalised has been subverted through such devices. His representation as a marginalised also would explore the community’s marginalised state in a hierarchical society.